Computing and Combinatorics : 5th Annual International Conference, COCOON’99 Tokyo, Japan, July 26–28, 1999 Proceedings - Asano, Takano; Imai, Hideki; Lee, D. T.; Nakano, Shin-ichi; Tokuyama, Takeshi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 1999)
The abstracts and papers in this volume were presented at the Fifth Annual International Computing and Combinatorics Conference (COCOON ’99), which was held in Tokyo, Japan from July 26 to 28, 1999. The topics cover most aspects of theoretical computer science and combinatorics pertaining to computing. In response to the call for papers, 88 high-quality extended abstracts were submitted internationally, of which 46 were selected for presentation by the p- gram committee. Every submitted paper was reviewed by at least three program committee members. Many of these papers represent reports on continuing - search, and it is expected that most of them will appear in a more polished and complete form in scienti c journals. In addition to the regular papers, this v- ume contains abstracts of two invited plenary talks by Prabhakar Raghavan and Seinosuke Toda. The conference also included a special talk by Kurt Mehlhorn on LEDA (Library of E cient Data types and Algorithms). The Hao Wang Award (inaugurated at COCOON ’97) is given to honor the paper judged by the program committee to have the greatest scienti c merit. The recipients of the Hao Wang Award 1999 were Hiroshi Nagamochi and Tos- hide Ibaraki for their paper \An Approximation for Finding a Smallest 2-Edge- Connected Subgraph Containing a Speci ed Spanning Tree".
Invited Talks -- The Web as a Graph: Measurements, Models, and Methods -- Some Observations on the Computational Complexity of Graph Accessibility Problem (Extended Abstract) -- Hao Wang Award Paper -- An Approximation for Finding a Smallest 2-Edge-Connected Subgraph Containing a Specified Spanning Tree -- Data Structures -- Theory of 2-3 Heaps -- An External Memory Data Structure for Shortest Path Queries (Extended Abstract) -- Computational Biology -- Approximating the Nearest Neighbor Interchange Distance for Evolutionary Trees with Non-uniform Degrees -- Signed Genome Rearrangement by Reversals and Transpositions: Models and Approximations -- Graph Drawing -- An Approximation Algorithm for the Two-Layered Graph Drawing Problem -- Area Minimization for Grid Visibility Representation of Hierarchically Planar Graphs -- Layout Problems on Lattice Graphs -- Discrete Mathematics -- A New Transference Theorem in the Geometry of Numbers -- On Covering and Rank Problems for Boolean Matrices and Their Applications -- A Combinatorial Algorithm for Pfaffians -- Graph Algorithms 1 -- How to Swap a Failing Edge of a Single Source Shortest Paths Tree -- On Bounds for the k-Partitioning of Graphs -- A Faster Algorithm for Computing Minimum 5-Way and 6-Way Cuts in Graphs -- Automata and Language -- Probabilities to Accept Languages by Quantum Finite Automata -- Distributionally-Hard Languages -- Circuits and Context-Free Languages -- Complexity Theory and Learning -- On the Negation-Limited Circuit Complexity of Merging -- Super-Polynomial Versus Half-Exponential Circuit Size in the Exponential Hierarchy -- Efficient Learning of Some Linear Matrix Languages -- Combinatorial Optimization 1 -- Minimizing Mean Response Time in Batch Processing System -- Approximation Algorithms for Bounded Facility Location -- Scheduling Trees onto Hypercubes and Grids Is NP-complete -- Graph Algorithms 2 -- Approximations of Weighted Independent Set and Hereditary Subset Problems -- Multi-coloring Trees -- On the Complexity of Approximating Colored-Graph Problems Extended Abstract -- Number Theory -- On the Average Sensitivity of Testing Square-Free Numbers -- Binary Enumerability of Real Numbers (Extended Abstract) -- GCD of Many Integers (Extended Abstract) -- Distributed Computing -- Multi-party Finite Computations -- Probabilistic Local Majority Voting for the Agreement Problem on Finite Graphs -- Combinatorial Optimization 2 -- A Dynamic-Programming Bound for the Quadratic Assignment Problem -- A New Approach for Speeding Up Enumeration Algorithms and Its Application for Matroid Bases -- Network Routing Problems -- On Routing in Circulant Graphs -- Minimum Congestion Embedding of Complete Binary Trees into Tori -- Computational Geometry -- Maximum Stabbing Line in 2D Plane -- Generalized Shooter Location Problem -- Online Algorithms -- A Competitive Online Algorithm for the Paging Problem with “Shelf” Memory -- Using Generalized Forecasts for Online Currency Conversion -- Rewriting Systems -- On S-Regular Prefix-Rewriting Systems and Automatic Structures -- Tractable and Intractable Second-Order Matching Problems -- Parallel Computing -- Efficient Fixed-Size Systolic Arrays for the Modular Multiplication -- Improving Parallel Computation with Fast Integer Sorting -- A Combinatorial Approach to Performance Analysis of a Shared-Memory Multiprocessor -- Combinatorial Optimization 3 -- A Fast Approximation Algorithm for TSP with Neighborhoods and Red-Blue Separation -- The Greedier the Better: An Efficient Algorithm for Approximating Maximum Independent Set.
SpringerLink.
Keywords: Computer science; Computer communication systems; Computer programming; Computers; Algorithms; Computer science. -- Mathematics; Computer graphics; Computer Science; Programming Techniques; Theory of Computation; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Computer Graphics